Comparison of Outcomes between Individuals with Pure and Mixed Lupus Nephritis: A Retrospective Study. - Titilayo O Ilori; Nosayaba Enofe; Anju Oommen; Jason Cobb; Jose Navarrete; Demilade A Adedinsewo; Oluwatobiloba Oshikoya; Helene Fevrier; Alton B Farris; Laura Plantinga; Akinlolu O Ojo (PLoS ONE, 2016)
Lupus nephritis (LN) is a serious organ manifestation of systemic lupus erythematosus. Histologic overlap is relatively common in the six pathologic classes (I to VI) of LN. For example, mixed proliferative LN (MPLN) often includes features of classes III & V or classes IV & V combined. We performed a comparative evaluation of renal outcomes in patients with MPLN to patients with pure proliferative LN (PPLN) against pre-specified renal outcomes, and we also identified predictor of clinical outcomes among those with PPLN and MPLN.Individuals with MPLN will have worse short-term renal outcomes compared to those with PPLN.We retrospectively reviewed 278 adult LN patients (≥18 years old) identified from an Emory University Hospital registry of native renal biopsies performed between January 2000 and December 2011. The final analytic sample consisted of individuals with a diagnosis of PPLN (n = 60) and MPLN (n = 96). We analyzed differences in clinical and laboratory characteristics at baseline. We also assessed associations between LN category and renal outcomes (complete remission and time to ESRD) with logistic and Cox proportional hazards models within two years of baseline.The study population was predominantly female (83.97%) and African American (71.8%) with a mean age of 33.4 years at baseline. Over a median follow up of 1.02 years, we did not find any statistically significant associations between MPLN and the development of ESRD or remission when compared to patients with PPLN (adjusted HR = 0.30, 95% CI = 0.07, 1.26).There was no association between mixed or pure histopathologic features of LN at presentation and rate of complete or partial remission but higher baseline eGFR was associated with a lower probability of complete remission among patients with lupus nephritis.